2020
DOI: 10.1111/flan.12438
|View full text |Cite
|
Sign up to set email alerts
|

The neoliberal logic of state seals of biliteracy

Abstract: State‐issued seals and certificates of biliteracy are increasingly common nationwide. Nevertheless, limited research to date has examined how this state legislation functions as language in education policy and the ideological foundations of these policies. Addressing this gap, the present paper examines state seals as an instance of neoliberal language education policy and addresses how the policy has been constructed in public discourse and interview narratives and how it has been implemented to date. Focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Unlike other districts that implemented the SoBL to appear innovative or as a way to compete with neighboring districts (Burnet, 2020), administrators in our study implemented the SoBL as an equity tool. Like the findings of Schwedhelm and King (2020), administrators viewed the SoBL as financially valuable for college credit and as a way to demonstrate their commitment to diversity. However, beyond implementing the SoBL as a way to “signal institutional virtue” (Schwedhelm & King, 2020, p. 13), interviews with administrators in our study suggested a personal dedication to supporting linguistically diverse students.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Unlike other districts that implemented the SoBL to appear innovative or as a way to compete with neighboring districts (Burnet, 2020), administrators in our study implemented the SoBL as an equity tool. Like the findings of Schwedhelm and King (2020), administrators viewed the SoBL as financially valuable for college credit and as a way to demonstrate their commitment to diversity. However, beyond implementing the SoBL as a way to “signal institutional virtue” (Schwedhelm & King, 2020, p. 13), interviews with administrators in our study suggested a personal dedication to supporting linguistically diverse students.…”
Section: Discussionmentioning
confidence: 66%
“…To date, three studies have investigated participation decisions—one at the state level (Subtirelu, Borowczyk, Thorson Hernández, & Venezia, 2019) one at the district level (Burnet, 2020), and one that included both (Schwedhelm & King, 2020). Through analysis of policy and promotional texts, Subtirelu et al (2019) found that following total school enrollment, the second strongest predictor of schools' participation in the SoBL program was the percentage of fluent English‐proficient students in the high school.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations